Alamandine: Potential Protective Effects in SARS-CoV-2 Patients - Soltani Hekmat, Ava; Javanmardi, Kazem (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Coronavirus disease 2019 (COVID-19) can occur due to contracting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 has no confined treatment and, consequently, has high hospitalization and mortality rates. Moreover, people who contract COVID-19 present systemic inflammatory spillover. It is now known that COVID-19 pathogenesis is linked to the renin-angiotensin system (RAS). COVID-19 invades host cells via the angiotensin-converting enzyme 2 (ACE2) receptor—as such, an individual’s susceptibility to COVID-19 increases alongside the upregulation of this receptor. COVID-19 has also been associated with interstitial pulmonary fibrosis, which leads to acute respiratory distress, cardiomyopathy, and shock. These outcomes are thought to result from imbalances in angiotensin (Ang) II and Ang-(1-7)/alamandine activity. ACE2, Ang-(1-7), and alamandine have potent anti-inflammatory properties, and some SARS-CoV-2 patients exhibit high levels of ACE2 and Ang-(1-7). This phenomenon could indicate a failing physiological response to prevent or reduce the severity of inflammation-mediated pulmonary injuries. Alamandine, which is another protective component of the RAS, has several health benefits owing to its antithrombogenic, anti-inflammatory, and antifibrotic characteristics. Alamandine alleviates pulmonary fibrosis via the Mas-related G protein-coupled receptor D (MrgD). Thus, a better understanding of this pathway could uncover novel pharmacological strategies for altering proinflammatory environments within the body. Following such strategies could inhibit fibrosis after SARS-CoV-2 infection and, consequently, prevent COVID-19.